Nature of Cretaceous dolerite dikes with two distinct: constraints on their linkage to mantle plumes and large igneous provinces from 40Ar/39Ar geochronology and geochemistry - Sinha, Anup K. (My University, 2019)
Two distinct sets of Cretaceous dolerite dikes intrude the Chhotanagpur gneissic complex of eastern India, mostly within the Damodar Valley Gondwanan sedimentary basins. One dike set trends NNE to ENE, whereas the other set, which includes the prominent Salma dike, trends NW to NNW. One dike from each set in the Raniganj Basin was dated using the 40Ar/39Ar method in order to resolve a controversy concerning the emplacement age of the Salma dike. The NE-trending dike yielded a plateau age of 70.5 ± 0.9 Ma, whereas the NNW trending Salma dike is much older, with a plateau age of 116.0 ± 1.4 Ma. These results demonstrate that the Salma dike was emplaced at ca. 116 Ma and not at ca. 65 Ma, as suggested in an earlier study. Geochemical characteristics of the two dikes are also distinct and indi cate that they belong to previously identified high-Ti and low-Ti dolerite groups, respectively. The observed geochemical characteristics of both dike sets are comparable with the geochemistry of basalts of the Kerguelen Plateau, Bunbury Island, and Rajmahal Group I and suggest a connection to mantle plumes. The new age data presented herein indicate that these two magmatic episodes in the eastern Indian Shield were related to the ca. 120–100 Ma Kerguelen mantle plume and its associated Greater Kerguelen large igneous province and the ca. 70–65 Ma Réunion plume and its associated Deccan large igneous province, respectively.
Keywords: Cretacious dolerite dikes, Damodar Valley, mantle plumes, igneous provinces, 40Ar/39Ar geochronology, geochemistry